Assessing the Challenges Encountered in Accessing Reproductive Health Services By Women: A Case Study Of Southern Division Kabale Municipality. - Tumuheirwe, Marion (Kabale University, 2024)
The study was about the challenges to women's access to reproductive health services in the southern division, of Kabale Municipality. The study was guided by objectives namely, to assess reproductive health services provided to women in the Kabale district, to investigate the challenges that limit women's access to reproductive health services in the Kabale district, and to find out the existing strategies for improving the women's accessibility to reproductive health services in Kabale district. The study used cross-sectional survey research design was used in the study. A total of 124 respondents were selected for the study. From the findings respondents showed that they had never received HIV Testing and Counseling (HTC) advice, it was revealed that respondents. Some respondents responded that Inadequate trained staff or transfer of trained and motivated staff resulted in a decrease in the commitment of the remaining staff. Some respondents showed that lack of privacy hinders women from seeking reproductive health services. According to the study, Lack of knowledge about condom use. Although the need for strong legal protection for women is clear, few interventions have been documented or evaluated. Some respondents also reported that this implies that there is a need to sign legal protection policies and regulations on those that misuse young girls and women, this will reduce the rate of conceiving". The study concludes that reproductive health is a critical component of any woman's health. It is widely acknowledged that reproductive health is a concern for all and more so for women, with a rise in cases of reproductive health issues. There is a need for understanding to mitigate negative societal attitudes towards the sexuality of women. Government and non-governmental organizations working in the area of reproductive health should conduct in-depth research and use the results to create awareness and advocate for policies and practices that can promote the sexual rights of women.